Educators’ attitudes towards inclusive education - Japundza-Milisavljevic, Mirjana; Đurić-Zdravković, Aleksandra; Milanović-Dobrota, Biljana (Specijalna edukacija i rehabilitacija, 2022)
The attitudes of educators towards inclusive education are a significant factor in successful education of students with disabilities. Objectives. The objectives of this research were to assess the attitudes of educators towards inclusion as well as to determine the differences in the attitudes between class teachers, primary school teachers and secondary school teachers. The specific objectives were to identify the differences in attitudes of teachers in relation to age and experience in working with students with disabilities. Methods. The survey was conducted on a convenient sample of 101 teachers, of both sexes (female 67.3% and 32.7% male), 24 to 53 years of age. Class teachers made up 38.6% of the sample, 33.8% were primary school teachers and 27.6% were secondary school teachers. Less than half of the respondents (43.6%) had experience in educating students with disabilities. A revised Opinions Relative to Integration of Students with Disabilities was applied. Results. The results indicate that most class teachers had a negative attitude, while the average scores of teachers in primary and secondary schools were grouped around neutral attitudes towards inclusive education. Younger teachers without experience in inclusive teaching believed that inclusive education was important for students with disabilities. Senior teachers recognized the problems of inclusive education. Conclusion. Based on the obtained data, we think that it is necessary to provide teachers with quality and continuous support of special educators in order to acquire informal experience, significantly reduce the number of students in classes, and provide material resources during inclusive teaching.
Keywords: teachers; attitude; experience in inclusive work